2020
DOI: 10.21203/rs.2.24079/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability in blood lipids affects the neutrophil to lymphocyte ratio in patients undergoing elective percutaneous coronary intervention: A retrospective study

Abstract: Background: Atherosclerosis is associated with chronic inflammation and lipid metabolism. The neutrophil to lymphocyte ratio (NLR) as an indicator of inflammation has been confirmed to be associated with cardiovascular disease prognosis. However, few studies have explored the effects of blood lipid variability on NLR. The aim of this study was to explore the relationship between variability in blood lipid levels and NLR. Methods: The association between variability in blood lipids and NLR was assessed with bot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The exact mechanism of these results remains unknown. One explanation is NLR is associated with the variability of cholesterol, rather than baseline cholesterol level ( 49 ). Further study is required to clarify the association between hyperlipidemia and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of these results remains unknown. One explanation is NLR is associated with the variability of cholesterol, rather than baseline cholesterol level ( 49 ). Further study is required to clarify the association between hyperlipidemia and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, in addition to the average level of blood lipids, the stability of lipid metabolism has also been considered critical. In our previous studies, it was found that the variation rate of LDL-C is signi cantly related to in ammation [13]. The study of Clark.D et al also found that the variation rate of LDL-C was an important indicator related to the progression of coronary atherosclerosis [23].…”
Section: Discussionmentioning
confidence: 95%
“…The stability index of lipid level may be another intuitive re ection of the individual's own lipid metabolism level. Our previous study has found that the variation rate of serum LDL-C and HDL-C levels are predictors of in ammation index NLR [13]. However, few studies concern the variability of non-HDL-C and Lp(a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some exploratory studies have suggested a possible link between cholesterol variability and inflammation, with HDL-C variability demonstrating particularly strong associations. (25,26) Given that inflammation plays important roles in the pathogenesis of heart failure, (27,28) this is a possible mechanism mediating the observed association between elevated HDL-C variability and elevated risk of heart failure. This was further supported by a recent study by Park et al who observed that both elevated C-reactive protein levels and HDL-C variability were associated with the risk of subclinical left ventricular diastolic dysfunction.…”
Section: Potential Underlying Mechanismsmentioning
confidence: 99%